Stress Elicits Contrasting Effects on Rac1-Cofilin Signaling in the Hippocampus and Amygdala - Bose, Mihika; Nawaz, Mohammad Sarfaraz; Pal, Rakhi; Chattarji, Sumantra (Frontiers in Molecular Neuroscience, 2022)
There is accumulating evidence for contrasting patterns of stress-induced morphological and physiological plasticity in glutamatergic synapses of the hippocampus and amygdala. The same chronic stress that leads to the formation of dendritic spines in the basolateral amygdala (BLA) of rats, leads to a loss of spines in the hippocampus. However, the molecular underpinnings of these divergent effects of stress on dendritic spines are not well understood. Since the activity of the Rho GTPase Rac1 and the actin-depolymerizing factor cofilin are known to play a pivotal role in spine morphogenesis, we investigated if alterations in this signaling pathway reflect the differential effects of stress on spine plasticity in the hippocampus and amygdala. A day after the end of chronic immobilization stress (2 h/day for 10 days), we found a reduction in the activity of Rac1, as well as its effector p21-activated kinase 1 (PAK1), in the rat hippocampus. These changes, in turn, decreased cofilin phosphorylation alongside a reduction in the levels of profilin isoforms. In striking contrast, the same chronic stress increased Rac1, PAK1 activity, cofilin phosphorylation, and profilin levels in the BLA, which is consistent with enhanced actin polymerization leading to spinogenesis in the BLA. In the hippocampus, on the other hand, the same stress caused the opposite changes, the functional consequences of which would be actin depolymerization leading to the elimination of spines. Together, these findings reveal a role for brain-region specific differences in the dysregulation of Rac1-to-cofilin signaling in the effects of repeated stress on two brain areas that are implicated in the emotional and cognitive symptoms of stress-related psychiatric disorders.